SOCIO-PEDAGOGICAL IMPORTANCE OF DEVELOPING COMMUNICATIVE COMPETENCE OF PRIMARY SCHOOL STUDENTS (Scientific journal of the Fergana State University, 2024)
In this article, the socio-pedagogical importance of developing the communicative competence of elementary school students is studied, its necessity and relevance today are covered in detail.